Conserving Spatially Explicit Benefits in Ecosystem Service Markets: Experimental Tests of Network Bonuses and Spatial Targeting. (6th January 2016) - Fooks, Jacob R.; Higgins, Nathaniel; Messer, Kent D.; Duke, Joshua M.; Hellerstein, Daniel; Lynch, Lori
Abstract : Conserving contiguous areas often enhances environmental benefits. However, most conservation efforts are incentive‐based and voluntary, and neither reward landowners for contiguity nor do they select based on contiguity. Thus, achieving optimal contiguity of conserved parcels is unlikely. Using lab and artefactual field experiments, this paper evaluates two mechanisms in the context of reverse auctions for achieving optimal contiguity: network bonuses and spatial targeting. Results suggest that spatial targeting alone improves the aggregate environmental and social welfare outcomes, while network bonuses alone result in worse outcomes. The interaction of the bonus effect and the targeting effect is positive. If a program was already using a competitive auction environment with bonuses, adding spatial targeting could reduce welfare loss.